PENGAMAN HELM DENGAN GPS MELALUI SMS BERBASIS MIKROKONTROLER ARDUINO UNO DENGAN SMARTPHONE - Adhitiya Saputra; Yohanes Dewanto (JURNAL TEKNOLOGI INDUSTRI, 2020)
At present the use of helmets is a safety in driving, although how to use and use is not so good if the helmet is lost, some people expect a tool or technology that can facilitate and help. With so many people interested in technology, many people want a helmet to stay in the vehicle parking lot, to avoid accidents when driving. But with so many people ignoring the incident, many also feel lost in the event of the loss of the helmet in the vehicle parking lot.Then made an arduino uno based helmet safety device via SMS, so that all feel safe in putting even leaving the helmet in the vehicle parking lot, because the system will do it automatically through the arduino uno and signal network to provide security for the helmet, before leaving the device must in the ON position or a ready tool that functions as a vibration detector sends data to Arduino Uno then the data enters the smartphone via sms to notify the helmet user and an SMS notification will appear on the smartphone via sms. Experiments prove the device that is made can function well if it gets results in smartphone sms lat = 6.34702348 & long = 106.86145019 and the tool can function if the signal network is good, if it functions poorly if the results in smartphone sms lat = 0.00000000 & long = 0, 0000000 and there is no good signal network due to weather disturbances. Keyword: helmet safety, SMS (SIM 800), Arduino uno, smartphone